2017
DOI: 10.1111/1750-3841.13592
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Antioxidants and Dietary Fiber in Edible Seaweeds

Abstract: Seaweeds are rich in different bioactive compounds with potential uses in drugs, cosmetics and the food industry. The objective of this study was to analyze macromolecular antioxidants or nonextractable polyphenols, in several edible seaweed species collected in Chile (Gracilaria chilensis, Callophyllis concepcionensis, Macrocystis pyrifera, Scytosyphon lomentaria, Ulva sp. and Enteromorpha compressa), including their 1st HPLC characterization. Macromolecular antioxidants are commonly ignored in studies of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 41 publications
(64 reference statements)
0
28
1
Order By: Relevance
“…Consequently, these compounds could provide protective effects over the pathogenesis of inflammatory diseases. Sanz-Pintos et al 6 analyzed the macromolecular antioxidants (or non-extractable polyphenols) of six edible seaweeds from Chile. They reported that this fraction possesses on average 42% of total polyphenol content and a remarkable antioxidant capacity.…”
Section: Health-promoting Activities Of Edible Seaweed Extracts From mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, these compounds could provide protective effects over the pathogenesis of inflammatory diseases. Sanz-Pintos et al 6 analyzed the macromolecular antioxidants (or non-extractable polyphenols) of six edible seaweeds from Chile. They reported that this fraction possesses on average 42% of total polyphenol content and a remarkable antioxidant capacity.…”
Section: Health-promoting Activities Of Edible Seaweed Extracts From mentioning
confidence: 99%
“…Despite the fact that Chile has a great variety of seaweeds, especially edible kinds, Chilean seaweed has been little exploited. Most research about Chilean seaweed has focused on nutritional aspects 9,10,11 or selected chemical compounds of interest 6,12,13,14,15 . No previous study has investigated the bioactivities of Chilean seaweed extracts.…”
Section: Health-promoting Activities Of Edible Seaweed Extracts From mentioning
confidence: 99%
“…Ofter the addition of algae to foods has a marked taste due to the presence of minerals, which, apart from functioning as pro-oxidant molecules, also produces undesirable metallic aromas. In addition to that, the content and type of fibers present in algae also contribute to both the colour and taste and the texture of the food (Sanz-Pintos et al, 2017;Atitallah et al, 2019) The sea bass fillets that were treated with SA1% (control) were globally accepted by 24% of the tasters and were evaluated in the second component (Figure 3), as they scored highest for taste, while intermediate scores were recorded for other attributes.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Despite the increase in the use of edible coatings on fruits and vegetables (Yosuf et al, 2018), the application of edible coatings for fish fillets is still limited. Thus, the use of edible alga-based coating may improve the nutritional value (the algae are rich in fibers, proteins, minerals, and vitamins) (Sanz-Pintos et al, 2017) and extend the shelf-life by minimizing oxidative reactions and growth of deteriorating microorganisms.…”
Section: Sensory Analysismentioning
confidence: 99%
“…and Enteromorpha sp. Macroalgae Polyphenols Macromolecular antioxidants [ 98 ] 7 Ecklonia stolonifera Macroalgae Phlorotannins, Oxylipins Matrix metalloproteinase (MMPs) inhibition activity [ 99 ] 8 Dunaliella salina, Chlorella species Microalgae Beta-carotene Photo-protective potential against UV, Anti-oxidant [ 100 , 101 ] 9 Muriellopsis sp. , Chlorella zofingensis, Scenedesmus sp.…”
Section: Algae and Associated Use In Cosmetic Productsmentioning
confidence: 99%